2005
DOI: 10.1111/j.1365-2400.2004.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestibility of angling baits for carp, Cyprinus carpio, with implications for groundbait formulation and eutrophication control

Abstract: To evaluate the suitability of angling groundbaits as a fish feed and the potential for nutrient loss, the macronutrient digestibility of four groundbaits was investigated in carp, Cyprinus carpio L., using a sieving method of faeces collection and chromic oxide. Apparent digestibility coefficients (ADCs) of protein and lipids were >80% for all angling baits. ADCs of nitrogen-free extracts and phosphorus (P) differed significantly between the test diets, probably because of divergent feed compositions and ingr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 15 publications
1
28
1
Order By: Relevance
“…Although some studies have addressed groundbaiting (e.g., Wolos et al 1992, Niesar et al 2004, Arlinghaus and Niesar 2005, Lewin et al 2006, we found no previous research that applied the modeling of reservoir water quality with simulations related to groundbaiting. We integrated SWAT (Neitsch et al 2002) …”
contrasting
confidence: 39%
See 1 more Smart Citation
“…Although some studies have addressed groundbaiting (e.g., Wolos et al 1992, Niesar et al 2004, Arlinghaus and Niesar 2005, Lewin et al 2006, we found no previous research that applied the modeling of reservoir water quality with simulations related to groundbaiting. We integrated SWAT (Neitsch et al 2002) …”
contrasting
confidence: 39%
“…Ordinary commercial groundbait is composed mainly of flours (e.g., corn, peanut, wheat), bread crumbs and crackers, aromatics, and dyes, in different proportions depending on the target species. Some studies indicate that the use of groundbait can negatively affect water quality and trophic status, cascading to other ecosystem components such as invertebrates (Wolos et al 1992, Niesar et al 2004, Arlinghaus and Niesar 2005, Lewin et al 2006. Nutrient enrichment of waterbodies and the consequent eutrophication effects are major problems for water quality in reservoirs (Smith et al 1999, Carpenter andLathrop 2008).…”
mentioning
confidence: 99%
“…revealed that the growth, density and fitness of the invasive fish, Pseudorasbora parva, was enhanced in pond mesocosms that received trophic subsidies in the form of small fishmeal pellets, with this often being an indirect mechanism as the elevated nutrient concentrations that occurred as a result of pellet introduction had the effect of increasing rates of algal standing stocks. Whilst the quantity of fishmeal pellets that were introduced into each river was not quantified, for comparative purposes it has been estimated that recreational anglers in Germany introduced a total of 24,000 tonnes of angling bait into freshwater fisheries in 2004 (Arlinghaus and Niesar 2005). This was not only believed to represent a significant trophic subsidy for the fish, but also elevated nutrient concentrations in the water and subsequently impacting adversely on water chemistry (Niesar et al 2004;Arlinghaus and Niesar 2005;Lewin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, pellets are increasingly being used by freshwater anglers in Europe as both an attractant and hook-bait to target fish of the Cyprinidae family, such as common carp Cyprinus carpio and European barbel Barbus barbus . Moreover, the quantities used can be substantial, with the amount of bait used annually per angler in Germany esti-mated at 7.3 kg (Arlinghaus and Niesar 2005). Given that these pellets were originally designed for feeding carniv-orous fish in aquaculture to maximise their growth through the input of an energy rich resource that is relatively easy to assimilate (Naylor et al 2000), then this at least partially explains their effective use within freshwater angling for a range of omnivorous and carnivorous species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation